Induction of metallothionein in the common bully ( Gobiomorphus cotidianus ) from the Motueka River - Louis A. Tremblay; Katherine Trought; Thomas J. Sheehan; Robin J. P. Holmes; Andrew Barrick; Roger G. Young (New Zealand Journal of Marine and Freshwater Research, 2021)
The Motueka catchment is a major river system in the South Island, New Zealand, typically considered to be of ‘good water quality’. The catchment has high metal inputs originating from a mineral belt in the headwaters. This study investigated the induction of metallothionein (MT) in the common bully, Gobiomorphus cotidianus , to assess exposure to trace metal contamination in the Motueka River. The results showed a significant increase in MT induction in both the gill and liver tissue samples from fish collected in the Motueka River compared to a reference site in the Brooklyn Stream tributary. This effect is likely modulated by the higher nickel levels originating from the Red Hills that accumulated in the sediment of the Motueka River.